EVALUASI DAMPAK REGIMEN BERBASIS CARBOPLATIN TERHADAP KUALITAS HIDUP PASIEN KANKER SERVIKS RAWAT INAP DENGAN MENGGUNAKAN KUESIONER EQ-5D (PHARMACON, 2016)
EVALUASI DAMPAK REGIMEN BERBASIS CARBOPLATIN TERHADAP KUALITAS HIDUP PASIEN KANKER SERVIKS RAWAT INAP DENGAN MENGGUNAKAN KUESIONER EQ-5D   Suwendar1,4), Achmad Fudholi2), Tri Murti Andayani2), Herri S. Sastramihardja3) 1)Program Studi S3 Fakultas Farmasi Universitas Gadjah Mada, Yogyakarta, Indonesia 2)Fakultas Farmasi,  Universitas Gadjah Mada, Yogyakarta, Indonesia 3)Fakultas Kedokteran, Universitas Padjadjaran, Bandung, Indonesia 4)ProgramStudi Farmasi Fakultas MIPA Universitas Islam Bandung Indonesia Korespondensi : suwendarrronnie@yahoo.com; fudholi_apt@ugm.ac.id ABSTRACT Cervical cancer is the cancer with high prevalence rates. The quality of life in patients with cervical cancer will decline. Decreasing of quality of life not only caused by cervical cancer itself, but also it can be caused by chemotherapy. Therefore, measurement of the quality of life of patients during chemotherapy is very important to avoid interventions ineffective. In this study, measurement of the quality of life for patients receiving chemotherapy with carboplatin-based regimen had been evaluated. Measurements were made using the EQ-5D questionnaire. Based on the measurements, it had been obtained the informations related to the quality of life that was the description of the percentage of patients who experienced problems in five aspects measured, the value of utility and value of the EQ-5D VAS. Five aspects  included  the ability of walking / mobility, self-care, usual activities, a sense of pain / discomfort and anxiety / depression. The percentage of patients who experienced a problem on every aspect had been compared before and after chemotherapy. Utility value and EQ-5D VAS had been compared statistically with a Wilcoxon signed rank test (p